(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the human, economic, and social losses caused by the Second World War and their long-term impact on global development based on scientific sources and historical statistical data. As a result of the war, millions of people lost their lives, major cities were destroyed, industry and agriculture collapsed, and the global economic system underwent fundamental changes. The study highlights the demographic consequences of the war, the scale of economic destruction, shifts in the global balance of power, the emergence of international organizations, and the factors that led to the beginning of the Cold War.